UPAYA PEMBUKTIAN OLEH JAKSA PENUNTUT UMUM DALAM TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN (ANALISIS PUTUSAN NOMOR:504/PID.B/2020/PN.SRH) - Sagala, Lamhot Heryanto; Nadirah, Ida (JURNAL DOKTRIN REVIEW, 2023)
The large number of criminal acts of theft occurring among Indonesian society has created a feeling of anxiety and fear of losing the property they own, therefore law enforcement efforts by the Prosecutor's Office must also be carried out seriously and professionally. The formulation of the problem is how to analyze the decision with aggravated theft in Decision Number: 504/Pid.B/2020/PN SRH, and what is the authority of the Prosecutor in trying to prove the crime of aggravated theft, as well as how to apply the law for the crime of aggravated theft in Decision Number: 504/Pid.B/2020/PN.Srh. The research method used is normative legal research. The legal provisions for the crime of aggravated theft are regulated in the provisions of Article 363 of the Criminal Code, categories of acts of theft that can be aggravated, due to the situation in which the theft is carried out, such as stealing livestock, stealing during riots, stealing at night, stealing from more than one perpetrator, and stealing by breaking into a house, and the Prosecutor's authority in trying to prove the crime of theft by aggravation, is as a functional official who is authorized by law to act as a public prosecutor and implement court decisions that have obtained permanent legal force and other authorities based on law. law, as well as the judge's consideration in the crime of theft with the aggravation of decision Number: 504/PID.B/2020/PN.SRH, that all the elements of Article 363 paragraph (1) 1st and 4th of the Criminal Code have been fulfilled and there is the Judge's confidence , then the Defendant must be declared to have been legally and convincingly proven as in the first alternative indictment. So, as a suggestion, the rules regarding criminal sanctions in the crime of theft with weights should be supplemented with compensation for losses experienced by the victim, and the prosecutor should be able to try to resolve theft cases through maximum restorative justice efforts.